Structural determinants for the interaction of lipopolysaccharide binding protein with purified high density lipoproteins: role of apolipoprotein A-I - T Massamiri; P S Tobias; L K Curtiss (Journal of Lipid Research, 1997)
The interaction of lipopolysaccharide binding protein (LBP) with apolipoprotein (apo)A-I on high density lipoproteins (HDL) was studied in solid phase ligand binding assays with a biotinylated LBP-specific antibody. The association was dependent on LBP concentration and enhanced in the presence of lipopolysaccharide (LPS). Maximal enhancement was measured at an LPS/LBP molar ratio of 6. To identify regions on apoA-I that participate directly or indirectly in the interaction between LBP and HDL, we attempted to inhibit LBP association with a panel of mapped apoA-I-specific monoclonal antibodies. Whereas some antibodies were effective inhibitors, others were not, even though they bound apoA-I. Furthermore, selected apoA-I synthetic peptides inhibited the antibody-mediated interference of the HDL/LBP interaction. Although no specific mechanism can be defined for the basis of the inhibitory effects of the antibodies on the association of LBP with HDL, we identified a role for three unique regions on apoA-I between residues 1-31, 95-164, and 178-200. These results suggested that apoA-I is a key component in the association of LBP with HDL and may play an important role in the biologic activity of LPS/LBP complexes.